2015
DOI: 10.1002/dc.23387
|View full text |Cite
|
Sign up to set email alerts
|

Cytomorphology is often insufficient to categorize non‐small‐cell lung carcinoma on FNA specimens

Abstract: Overall, the low interobserver agreement in our study indicates that accurate subclassification between the NSCLCs often cannot be made by cytomorphology alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…This may be the reason why the positive rate of RT-PCR is higher than the IHC method. Tumor tissue biopsy samples are the main sample types for clinical testing, including bronchoscopy, ultrasound bronchoscopy or percutaneous lung biopsy [37,38]. However, tissue biopsy has many limitations.…”
Section: Discussionmentioning
confidence: 99%
“…This may be the reason why the positive rate of RT-PCR is higher than the IHC method. Tumor tissue biopsy samples are the main sample types for clinical testing, including bronchoscopy, ultrasound bronchoscopy or percutaneous lung biopsy [37,38]. However, tissue biopsy has many limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Subsolid nodules were associated with higher odds of false-negative biopsy (OR 3.95), while granulomatous inflammation and documentation of needle tip within target were associated with lower odds of false negative biopsy (OR 0.04 and 0.37, respectively). Further, Witt and colleagues studied 50 cases of NSCLC diagnosed by FNA with concurrent core biopsy or resection as a reference standard (57). They found that interobserver agreement in classifying cases as squamous cell or adenocarcinoma was poor at 0.22 when an indeterminate category was included and 0.1 when it was not, with overall accuracy for differentiating these two pathologies at 65% and 66% respectively.…”
Section: Minimally Invasive Methods To Biopsy Ipnsmentioning
confidence: 99%
“…A small biopsy involves taking a small piece of diseased tissue for pathologic examination for the purposes of obtaining a preoperative diagnosis and optimizing the corresponding treatment. The means for this type of sampling include bronchial fiberscopic techniques, ultrasonic bronchoscopy or percutaneous lung biopsy [ 15 , 16 ]. The advantages of small biopsies are that they are minimally invasive, simple operations with fewer complications and greater patient acceptance that can generally be performed as outpatient procedures.…”
Section: Introductionmentioning
confidence: 99%